Control of Colletotrichum coccodes on Tomato by Grafting and Soil Amendments. Issue 2 (10th August 2013) - Gilardi, Giovanna; Colla, Paola; Pugliese, Massimo; Baudino, Michele; Gullino, Maria Lodovica; Garibaldi, Angelo
Abstract Eight trials were carried out in 2011 and 2012 in Northern Italy to evaluate the efficacy of grafting, compost and biofumigation with Brassica carinata against Colletotrichum coccodes on tomato. Four trials were carried out in commercial farms, and four trials were carried out in plastic tunnels at an experimental centre. The rootstocks 'Armstrong', 'Arnold', 'Beaufort', 'Big Power', 'Brigeor', 'Emperador', 'King Kong', 'Spirit' and 'Superpro V295' were tested. Host plants included several tomato F1 hybrids: 'Amantino', 'Arawak', 'CLX 37438', 'Cauralina', 'CU 8301', 'CU 8506', 'DRK 7021', 'E 34431', 'E 50070', 'EXP', 'Gotico', 'Ingrid', 'ISI 61401', 'ISI 61402', 'Profitto', 'Punente', 'Rugantino' and 'Tomahawk'. Tomato roots from the control plots were 34 to 87% diseased in both naturally and artificially infested soil. Among the nineteen commercial tomato hybrids tested, in the presence of a very high disease pressure in a naturally infested soil, 'Rugantino' was the least affected by C. coccodes, showing 32% infected roots. 'Tomahawk' grafted onto 'Arnold', 'Armstrong' and 'Superpro V295' was significantly less affected by C. coccodes, while 'Arawak' grafted onto 'Armstrong', 'Arnold', 'Emperador' and 'Beaufort' provided very good control of root rot in the different trials. Compost addition and biofumigation with Brassica pellets were also tested with and without grafting. Soil amendment with compost, in the case of the 'Arawak' and 'Tomahawk', resulted in a slightly improved disease control only on non‐grafted plants. When grafting and biofumigation were combined in a soil naturally infested with C. coccodes and Meloidogyne arenaria, biofumigation did not improve C. coccodes control in comparison with grafting alone. In a naturally infested soil, compost alone and combined with biofumigation improved disease control only on non‐grafted 'Tomahawk' plants. In general, grafting by itself provided very good results in terms of disease control, which were not significantly improved by combination with compost and/or biofumigation.